Three-dimensional echocardiographic ventricular mass/end-diastolic volume ratio in native hypertensive patients: relation between stroke volume and geometry. Issue 8 (August 2018) - Lembo, Maria; Esposito, Roberta; Santoro, Ciro; Lo Iudice, Francesco; Schiano-Lomoriello, Vincenzo; Fazio, Valeria; Grimaldi, Maria Gabriella; Trimarco, Bruno; de Simone, Giovanni; Galderisi, Maurizio
Abstract : Background: Elevated left ventricular (LV) mass/end-diastolic volume ratio (LVM/EDV) has been associated with higher evidence of myocardial fibrosis and dysfunction in hypertensive patients by cardiac magnetic resonance, a technique with limited availability. Objectives: We investigated the ability of three-dimensional (3D) echocardiography in identifying a phenotype of LV concentric geometry according to LVM/EDV ratio, possibly detecting early myocardial damage in native-hypertensive patients. Methods: One hundred and twenty-eight native-hypertensive patients underwent 2D and 3D-echocardiography. The population was divided into two groups, according to cut-off point values of 3D-LVM/EDV ratio corresponding to its upper 95% confidence interval in a population of 90 healthy normotensive individuals: LVM/EDV ratio cut-off was 1.22 in men and 1.23 in women. Results: An increased 3D-LVM/EDV ratio identified a higher rate of LV concentric geometry in comparison with 2D-derived relative wall thickness (37 versus 24%, P  = 0.03). Patients with LVM/EDV ratio of 1.22 or more in men and 1.23 or more in women were significantly older, had smaller 3D-LV end-diastolic and end-systolic volumes and higher LV mass index, without difference in ejection fraction. 3D-stroke volume ( P  < 0.0001) was lower in patients with elevated LVM/EDV ratio. By a multilinear regression analysis, after adjusting for sex, age, heart rate, mean blood pressure and BMI, stroke volume was independently and negatively associated to LVM/EDV ratio ( β  = −0.55, P  < 0.0001). Conclusion: In native hypertensive patients, 3D-echo-derived LVM/EDV ratio identifies a higher prevalence of LV concentric geometry than 2D-relative wall thickness. Stroke volume is independently and negatively associated with LVM/EDV ratio and its reduction represents an early marker of myocardial dysfunction in hypertensives with LV concentric geometry.